Perception of National Identity in a Group of University Students in Yogyakarta, Indonesia - Supratiknya, Augustinus (Journal of Leadership, Accountability and Ethics, 2024)
National identity is critical in a multi-ethnic country like Indonesia. This research of 75 second-year psychology students in Yogyakarta, Indonesia, investigates conceptions of national identity. Employing Rusciano's Selbstbild and Guibernau's five-dimensional theory, an email survey with three open-ended questions was utilized. Thematic analysis revealed prevalent themes among respondents, primarily within the political dimension of national identity. Noteworthy were notions of respecting diversity, safeguarding rights and privacy, opposing discrimination, and combatting intolerance. The diverse ethnic and religious backgrounds of participants underscored Indonesia's multiethnic landscape. The findings highlighted a heightened political commitment among female participants compared to males. In essence, this study illustrates the applicability of Guibernau's five-dimensional theory in comprehending the nuanced development of national identity in a diverse sample of Indonesian university students.